EFFECTIVENESS OF IMPLEMENTATION OF HUMAN RESOURCES MANAGEMENT DURING THE COVID-19 PANDEMIC ON EMPLOYEES MOVING IN THE FORMAL SECTOR IN INDONESIA - Pambudy, Akhlis Priya; Sopiah, Sopiah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Organizations and their human resources must navigate through the harsh impacts of the new coronavirus disease (COVID-19). The external crisis required the dynamism of the HR system to address the growing concerns of all sectors around the world and in particular, Indonesia's formal sector and its employees. The HR department serves as a liaison between organizations and their human resources. Therefore, HR Officers need to ensure a balance between the benefits of the parties in the employment contract. Since the employer aims to maximize profits, the employee aims to maximize job satisfaction. In an effort to ensure that both parties are well served after the COVID-19 crisis period, there is a need to reintegrate existing human resource practices and procedures. Getting past crises will require learning, innovation, and adaptation. HR practices need to be modified, rebuilt, and put into practice. In this article, we discuss the challenges employers and employees face in dealing with the pandemic and how these challenges can be mitigated through readjustment of HR practices taking into account the local Indonesian context. Such evidence requires a rapid response for the HR department to adapt HR practices to align with the crisis. We recommend empirical research in this area to assist long-term HR policy.